ANALISIS PENGARUH KOMPETENSI KOMUNIKASI, KECERDASAN EMOSIONAL DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN (STUDI PADA PT. BANGUN JAYA ALAM PERMAI I, DI KOTAWARINGIN BARAT) - Utomo, Budi (JURNAL EKOMAKS : Jurnal Manajemen, Ekonomi Kreatif dan Bisnis, 2019)
Basicly, the employee performance are the result of a complex processes, which are come from the employees itself (internal factor), company situation (external factor), and the company strategic efforts. A good performance is certainly being expected all company and institution who employ the employees, because the employee performance finally expected to increase the company performance totality. This research is aimed to examine the impact of communication competence, emotional intelligence, and organizational culture to employee performance. The problem raised in this study are (1) The influence of communication competence on employee, (2) The influence of emotional intelligence on employee performance, (3) The influence of organizational culture on employee performance.This research has been conducted in PT Bangun Jaya Alam Permai I District of Kotawaringin Barat, Province of Central Kalimantan. As many as 40 employees are taken as respondent using disproportionate stratified sampling. Questionnaires were used as a tool in data collection method. Data analysis techniques in this research SPSS 20 for Windows.This research gets some important conclusion. Firstly, all hypotheses were proved to be significant. Secondly, all of variables communication competence, emotional intelligence and organizational culture impact on employee performance. The implies that communication competence, emotional intelligence and organizational culture played as important role in developing employee performance